Autistic Traits, Language & Cognition in Bidialectal Individuals - Antoniou, Kyriakos; Petinou, Kakia (My University, 2023)
This research aims to examine (1) the reliability and validity of two questionnaires measuring autistic traits—the Autism-Spectrum (AQ) [1] and Systemizing Quotient (SQ) [2]—in neurotypical, young-adult bidialectal participants who speak two Greek dialects—Cypriot and Standard Modern Greek; and (2) the effect of autistic traits on aspects of verbal and non-verbal cognition—vocabulary and non-verbal fluid intelligence, respectively—in the same sample. Past research has examined the linguistic and cognitive effects of Autism Spectrum Disorder and of autistic traits in monolingual and, to a lesser extent, in bilingual speakers [e.g., 3, 4]. However, to date, there has been no comprehensive examination of how autistic traits impact language and cognition in bidialectal individuals [though see e.g., 5]. Moreover, widely-used questionnaires for quantifying autistic traits and for identifying individuals who possibly need clinical referral for full diagnosis of the Autism Spectrum Disorder—including the AQ and SQ—have typically been developed for use with English-speaking and with monolingual individuals [e.g., 1, 2]. Thus, it is an open empirical question whether such questionnaires are appropriate for use with speakers of other languages or dialects (e.g., Greek) and, importantly, with bidialectal individuals. Based on past research indicating that autistic individuals frequently exhibit an uneven cognitive profile with higher perceptual but lower verbal reasoning [3, 6], we predicted similar effects of autistic traits within our bidialectal sample; that is, a negative effect on vocabulary but no effect on non-verbal fluid intelligence. One hundred and sixty-three young adults (mean age=22, SD=4.4, 37 male) took the ΑQ, SQ, WASI matrix reasoning (WASI) [7], Standard Progressive Matrices (SPM) [8] non-verbal fluid intelligence tasks, and a vocabulary test. More data is currently being collected. Both quotients showed adequate overall internal reliability (Cronbach’s α=.71 and .90, respectively) but internal consistency was low for the separate AQ sub-scales (α from .41 for Imagination to .64 for Attention to Detail). Also, the quotients correlated significantly (r=.19, p(two-tailed)<.05), consistent with past research in English [2]. We formed composite scores for related variables by averaging relevant z-transformed measures (in parentheses): Autism (AQ, SQ total) and fluid intelligence scores (WASI, SPM). There was a small-to-medium but non-significant gender effect on Autism score indicating higher autistic traits for males than females (F(1,152)=1.80, p>.05, Cohen’s d=.29), again, partly in line with previous work [1, 2]. Finally, higher autistic traits had a marginally non-significant negative effect on vocabulary (r=-.18, p(two-tailed)=.074) but no significant effect on fluid intelligence (r=-.06, p(twotailed)>.05). While this research is still ongoing and more data is being collected, our results suggest that similar effects of autistic traits as previously reported for English-speaking monolingual individuals seem to hold for Greek-speaking bidialectal speakers. Moreover, the AQ and SQ are useful tools for quantifying autistic traits in this sample. We are currently conducting additional analyses to examine how autistic traits interact with different bidialectal experiences (e.g., degree of dialect/language switching or of using a second dialect/language) in affecting language and non-verbal cognition. Future work should also investigate the potential of the AQ and SQ for screening individuals possibly having the Autism Spectrum Disorder.